Gut microbiome analysis in human living close to livestock at Mlati district, Sleman, Yogyakarta - Sari, Yulia; Suryawati, Betty; Probandari, Ari; Hartono, Hartono; Artama, Wayan Tunas; Purwanto, Bambang; Soetrisno, Soetrisno (Sanglah General Hospital, 2022)
Background: Transmission of pathogenic and non-pathogenic microorganisms from animals to humans can affect the composition of gut bacteria (gut microbiome) in humans and can also be a potential source of transmission of zoonotic diseases. Therefore, this study aimed to analyze the gut microbiome interactions between the human and the livestock. Method: This study was a cross-sectional study conducted in Mlati District, Slemanm Yogyakarta. The fecal sample was used to identify parasites by using trichrome staining. Then NGS selected samples were used to analyze the gut microbiome using Illumina high throughput 16S rRNA region V3-V4 sequencing. Result: The analysis showed that Bacteroidetes was prevalent in the HCA group (57%), while Firmicutes (70%) were commonly found in HNC. Regarding the potential parasitic infection, direct microscopic examination and trichrome staining showed that Blastocystis sp and Entamoeba coli cyst was found in several subjects in HCA groups, with prevalence rate at 7.69% and 2.5%. Meanwhile, no parasite was found in HNC feces. Conclusion: There was a significant difference in the gut microbiome and parasitic infections between the HCA and HNC groups, with Blastocystis sp and Entamoeba coli as the most prevalent parasites.